Synthesis of novel thiosemicarbazone derivatives as antidiabetic agent with enzyme kinetic studies and antioxidant activity - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (My University, 2022)
Novel thiosemicarbazone derivatives were synthesized via condensation reactions between the corresponding thiosemicarbazides and 4-(methylsulfonyl)acetophenone. The chemical structures of all compounds were elucidated by infrared (IR), H-1-NMR and C-13-NMR spectroscopy and mass spectrometry. Antioxidant studies of all compounds were performed by using CUPRAC, FRAP, DPPH methods. 2-{1-[4-(Methylsulfonyl)phenyl]ethylidene}-N-phenylhydrazinecarbothioamide (1) possessed good antioxidant activity with an SC50 value of 15.70 mu M which also is higher than standard drug, ascorbic acid. All compounds were evaluated for their antidiabetic properties as alpha-glycosidase and alpha-amylase inhibitors. Compound 1 was found to be the most active compound against alpha-glucosidase and alpha-amylase with IC50 values of 1.58 mu M and 3.24 mu M, respectively. The enzyme kinetic studies demonstrated that compound 1 has a competitive mode of binding. Furthermore, molecular docking studies have elucidated the binding mechanism at the molecular level by examining the molecular interactions between compound 1 and these enzymes.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; İnorganik Kimya; Temel Bilimler; Chemistry; Biochemistry; Bioinorganic Chemistry; Inorganic Chemistry; Natural Sciences; KİMYA, İNORGANİK VE NÜKLEER; Temel Bilimler (SCI); KİMYA, ORGANİK; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, ORGANIC; Organik Kimya; İnorganik kimya; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Organic Chemistry; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Thiosemicarbazones; alpha-glucosidase; alpha-amylase; antioxidant; molecular docking; ALPHA-AMYLASE; GLUCOSIDASE INHIBITORS; DISCOVERY; OXIDASE; α-amylase; α-glucosidase; Thiosemicarbazones; a-glucosidase; a-amylase; antioxidant; molecular docking